2021
DOI: 10.1103/physrevc.104.l011302
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the N=50 and Z=28 shell closure

Abstract: Recent experiments performed in neutron-rich copper isotopes have revealed a crossing in the nucleus 75 Cu between the 3/2 − and 5/2 − levels, which correspond to the ground state and the first excited state in isotopes with mass number below A = 75. Due to the strong single-particle character of these states, this scenario can be investigated through the analysis of the proton spectrum provided by mean-field models in nickel isotopes with neutron numbers between N = 40 and N = 50. In this work, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The mean-field calculation have been performed within the QLDFT framework using the uniform blocking method to describe odd nuclei. This approximation is justified, as far as we have shown in a recent work [18], QLDFT and HF calculations give identical results in N i-isotopic series. It is shown that in case of the SEI interaction with an incompressibility value K(ρ 0 )=240 MeV, there is no requirement of explicit inclusion of a tensor part, unlike the case in Gogny and Skyrme forces, to achieve the 2p 3/2 and 1f 5/2 s.p.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The mean-field calculation have been performed within the QLDFT framework using the uniform blocking method to describe odd nuclei. This approximation is justified, as far as we have shown in a recent work [18], QLDFT and HF calculations give identical results in N i-isotopic series. It is shown that in case of the SEI interaction with an incompressibility value K(ρ 0 )=240 MeV, there is no requirement of explicit inclusion of a tensor part, unlike the case in Gogny and Skyrme forces, to achieve the 2p 3/2 and 1f 5/2 s.p.…”
Section: Discussionsupporting
confidence: 74%
“…Notice that the presence of a tensor term does not guarantee the crossing of these s.p. proton levels, as is the case of the Skyrme-Lyon force SLy5, as has been discussed recently in [18]. This fact point out the relevance of the underlying mean-field to describe the crossing of the aforementioned s.p.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations